Predatory mortgage lending - Bond, Philip; Musto, David K.; Yilmaz, Bilge (Journal of Financial Economics, 2009)
Regulators express growing concern over predatory loans, which we take to mean loans that borrowers should decline. Using a model of consumer credit in which such lending is possible, we identify the circumstances in which it arises both with and without competition. We find that predatory lending is associated with highly collateralized loans, inefficient refinancing of subprime loans, lending without due regard to ability to pay, prepayment penalties, balloon payments, and poorly informed borrowers. Under most circumstances competition among lenders attenuates predatory lending. We use our model to analyze the effects of legislative interventions.